Computer simulation of control strategies for optimal anaerobic digestion. - Strömberg, S. (Water Science and Technology)
Three previously published control strategies for anaerobic digestion were implemented in Simulink/Matlab using Anaerobic Digestion Model No. 1 (ADM1) to model the biological process. The controllers? performance were then simulated and evaluated based on their responses from five different types of process scenarios i.e. start-up and steady state performance as well as disturbances from concentration, pH and ammonia in the inflow. Of the three evaluated control strategies, the extremum-seeking variable gain controller gave the best overall performance. However, a proportional feedback controller based on the pH-level, used as a reference case in the evaluation, proved to give as good results as the extremum-seeking variable gain controller but with a lower wear on the pump. It was therefore concluded that a fast proportional control of the reactor pH is a key element for optimally controlling a low-buffering anaerobic digestion process.